Comparison of Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in Pediatric Acute Lymphoblastic Leukemia Patients Before and After Induction Chemotherapy - M. Arie Wibisono; Olga Rasiyanti Siregar; Fera Wahyuni; Juliandi Harahap; Bidasari Lubis; Fathia Meirina (GLOBAL HEALTH SCIENCE GROUP, 2026)
Acute Lymphoblastic Leukemia (ALL) is the most common hematologic malignancy in children. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple inflammatory biomarkers that may serve as prognostic and therapeutic response indicators. The aim of this research is to evaluate the differences in NLR and PLR before and after induction chemotherapy and to determine optimal cut-off values for predicting treatment response in pediatric ALL patients. An observational analytic study with a retrospective design was conducted on 48 pediatric ALL patients at Adam Malik General Hospital, Medan. Data were obtained from medical records between January 2023 and December 2024. Consecutive sampling was applied on this study. The Wilcoxon test was applied to assess differences in NLR and PLR, while ROC analysis was used to determine cut-off values, sensitivity, and specificity. Most patients were under 10 years of age (66.7%) and male (58.3%). Following induction chemotherapy, 87.5% achieved complete remission. Significant differences in NLR and PLR were observed before and after therapy (p<0,001). The optimal cut-off for NLR was 2.33 (sensitivity 45.2%, specificity 83.3%), while for PLR it was 219.98 (sensitivity 42.9%, specificity 83.3%). NLR and PLR significantly changed after induction chemotherapy in pediatric ALL patients. Despite limited sensitivity, both markers may serve as simple hematological tools for evaluating treatment response.